Conhecimentos docentes e tecnologias digitais: perspectivas para a formação do professor de Química - Cavassani, Thiago Bernardo (2021)
The present research was conducted through a formative pedagogical intervention work promoting the insertion of digital tools articulated to the teaching of content and pedagogical practices to undergraduate students of a chemistry major at a federal educational institution. The objective of this work was to investigate the ways undergraduates interact with different digital resources throughout interventional activities, considering the relations between domain/appropriation of technologies and possible implications in pedagogical and content aspects that compose the professional teaching body of knowledge. The theoretical and methodological delimitation were based on the concept that professional teachers are engaged in a formative continuum; additionally, on the contributions about the interrelation between technologies and education, and the TPACK framework in an approximation with the sociocultural approach. The work was developed in two regular courses in the discipline of chemistry from a qualitative research perspective. As a result, we highlighted elements that point at new ways of relating students with the space and time of learning, in the articulation between ICT, the didactic proposals and the disciplinary contents. Different forms of mastery and levels of appropriation of cultural tools were identified, as well as signs of TPACK development in the teaching activities developed by the undergraduates. However, gaps in the undergraduate’s TPACK were also evidenced, especially regarding the understanding of chemical knowledge for social activity and in the relationship between the proposed pedagogical activities and the selected digital technologies. The elaboration of meanings of this process evidences important aspects of appropriation of ICT and development of TPACK, as well as a tense relationship between ICT and the possibilities for teaching chemistry. It is important to encourage the integration of ICT in the training process to interrelate digital technologies and subject content at different times throughout the initial training, as well as to provide opportunities for critical and reflective analysis in order to allow its continuous significance. With these actions, it is possible to foster a true pedagogical appropriation of these cultural tools by teachers in training.